Pemahaman Tentang Hak Dan Kewajiban Peserta BPJS Kesehatan Di Puskesmas Ganding Sumenep - Moh. Jonaidy Prasetiawan; Dr. Eko Mulyadi; Sugesti Aliftitah (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2019)
The large number of BPJS Kesehatan participants who do not understand the rights and responsibilities of BPJS Kesehatan participants, make medical workers in health facilities often conflict with patients and families of patients. This research was conducted to describe the understanding about the rights and obligations of BPJS Kesehatan participants. The method in this research is qulitative descriptive research, this research is intended to investigate the condition, condition or other matters, which result presented in the form of research report. Lack of understanding of BPJS Kesehatan participants due to the absence of clear, correct, detailed and detail information regarding regulations, financing, rights and obligations, sanctions if late dues, health facility destinations, tiered referral, emergency services, how to submit complaints, or concerning health services anything that can and can not be obtained. BPJS Kesehatan socializes passively, which is only doing socialization if invited to come by interested parties. According to Law No. 08 of 1999 on Consumer Protection, BPJS Kesehatan as a business actor is obliged to provide information and socialization that is clear, true and honest about the product of goods or and services to be provided, should not cause the interpretation, must be clear, detailed, and detail. Keyword: Rights, Responsibilities, Socialization, BPJS Kesehatan.